The treatment of falciparum malaria in children with halofantrine suspension - R. J. Horton; S. N. Parr; L. C. Bokor (Memorias do Instituto Oswaldo Cruz, 1992)
Malaria treatment of children is particulary difficult because of the absence of palatable suspensions for young children. Halofantrine hydrochloride is available as a suspension which is both palatable and simple to administer, and has been studied in a number of trials in the past 5 years. Children (331) ranging from 4 months to 17 years of age (mean 4.7 years) were treated with the 5% suspension using various dose regimens and 364 children ranging from 4 months to 14 years of age (mean 5.7 years) were treated with the 2% suspension 6 hourly for 3 doses. Using the 3-dose regimen there were only 2/462 (0.4%) who failed to clear the initial parasitaemia. Recrudescence occurred in 28/367 (7.6%) children with evaluable follow up data. The mean parasite clearance time in this group was 57.1h (n = 417) and the mean fever clearance time was 50.9 h (n = 325). Symptoms related to malaria cleared rapidly following treatment generally by 24-48 h post treatment. Side effects possibly related to treatment were uncommon but were similar to those reported in adults. The frequency of diarrhoea and abdominal pain was lower than that seen in adults and was also less frequent following multiple doses and the use of the more dilute suspension. Since was evidence that the majority of recrudescences were seen in younger children or those living in areas with low or seasonal transmission it is recommended that a further course of treatment 7 days later is given to these patients to prevent recrudescence. Halofantrine suspension appears to be effective and well tolerated in children and is a useful addition to the drugs available for the treatment of paediatric malaria.